20 Chinese translation and validation of scales for left ventricular assist device (LVAD) self-efficacy and adherence. (9th April 2018) - Cheng, Lily L; Sit, Janet WH
Abstract : Left ventricular assist device (LVAD) is an alternative therapy for patients with end-stage heart failure. Patients with LVADs must manage a complex regimen of care, including activities regarding self-care maintenance (e.g., activities related to lifestyle and LVAD system operation), self-care monitoring (e.g. monitoring for LVAD device/system and complications), self-care management (e.g. handling alarms). Emerging data have indicated the increasing use of LVAD among patients in the Chinese-speaking population. Instruments that specifically measure self-efficacy for and adherence to LVAD care regimen are required to identify the unmet needs of patients and advance the science of LVAD care in Chinese-speaking countries. Here, we report the translation and initial validation of four measurement instruments designed to assess the self-efficacy for and adherence to the LVAD care regimen of patients and their care-givers. A validation study plan and the research and practice implications of the four measurement instruments in emerging Chinese-speaking populations are discussed.